Combined amendment of immobilizers and the plant growth-promoting strain Burkholderia phytofirmans PsJN favours plant growth and reduces heavy metal uptake. (December 2015) - Touceda-González, María; Brader, Günter; Antonielli, Livio; Ravindran, Vivek Balakrishnan; Waldner, Georg; Friesl-Hanl, Wolfgang; Corretto, Erika; Campisano, Andrea; Pancher, Michael; Sessitsch, Angela
Abstract: In the surroundings of a former Pb/Zn smelter in Arnoldstein (Austria) heavy metal concentrations in planted crops exceed thresholds for usage as food and feed. The aim was to study the effects of a plant growth-promoting bacterial strain in combination with immobilizing soil amendments on plant growth, heavy metal uptake and on microbial community structure. Pot experiments were performed whereby two maize cultivars were grown in different contaminated soils and treatments consisted of Burkholderia phytofirmans strain PsJN with and without addition of gravel sludge and siderite bearing material. Inoculation with strain PsJN significantly improved root and shoot biomass of maize independent of immobilizer addition. Analysis of heavy metal content of the rhizosphere and leaves indicated that immobilizing amendments had significant reducing effects on NH4 NO3 extractable Zn and Pb in soil and in plants grown in treated soils. Microbiomes were analysed by cultivation-independent pyrosequencing analysis of 16S rRNA genes. The results showed clear effects on community composition in response to the immobilizer amendments, whereas inoculation with B. phytofirmans affected microbiome diversity only to a minor extent. Highlights: Immobilizer amendment reduced heavy metal availability and plant uptake. Burkholderia phytofirmans strain PsJN increased plant biomass production even in heavy metal contaminated soil. The immobilizer amendment affected rhizosphere microbiomes leading to higher diversity. B. phytofirmans strain PsJN inoculation alone had only minor effects on alter microbiome structures.